2015
DOI: 10.1038/mp.2015.177
|View full text |Cite
|
Sign up to set email alerts
|

APOE*E2 allele delays age of onset in PSEN1 E280A Alzheimer’s disease

Abstract: Alzheimer's disease (AD) age of onset (ADAOO) varies greatly between individuals, with unique causal mutations suggesting the role of modifying genetic and environmental interactions. We analyzed ~50 000 common and rare functional genomic variants from 71 individuals of the ‘Paisa' pedigree, the world's largest pedigree segregating a severe form of early-onset AD, who were affected carriers of the fully penetrant E280A mutation in the presenilin-1 (PSEN1) gene. Affected carriers with ages at the extremes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 56 publications
10
90
0
Order By: Relevance
“…Sun et al next examined the relationship between the Aβ42/Aβ40 ratio and the age of disease onset associated with individual mutations and found no significant correlation, further arguing against the pathogenicity of a heightened Aβ42/Aβ40 ratio. However, it should be noted that age of onset is an imperfect proxy for the pathogenicity of individual mutations; for example, the age of onset ascribed to a given FAD mutation is often based on small numbers of affected individuals and can vary substantially based on APOE genotype and possibly other modifier effects (16,17). In contrast, mean ages of onset derived from large numbers of mutations identified in PSEN1 and APP might offer insight into the relative pathogenicity of mutations in each gene; a recent meta-analysis of 1,300 individuals with PSEN or APP mutations demonstrated that PSEN1 mutations cause FAD with a significantly earlier mean age of onset than APP mutations (18).…”
Section: Loss Of γ-Secretase Activity By Psen1 Mutationsmentioning
confidence: 99%
“…Sun et al next examined the relationship between the Aβ42/Aβ40 ratio and the age of disease onset associated with individual mutations and found no significant correlation, further arguing against the pathogenicity of a heightened Aβ42/Aβ40 ratio. However, it should be noted that age of onset is an imperfect proxy for the pathogenicity of individual mutations; for example, the age of onset ascribed to a given FAD mutation is often based on small numbers of affected individuals and can vary substantially based on APOE genotype and possibly other modifier effects (16,17). In contrast, mean ages of onset derived from large numbers of mutations identified in PSEN1 and APP might offer insight into the relative pathogenicity of mutations in each gene; a recent meta-analysis of 1,300 individuals with PSEN or APP mutations demonstrated that PSEN1 mutations cause FAD with a significantly earlier mean age of onset than APP mutations (18).…”
Section: Loss Of γ-Secretase Activity By Psen1 Mutationsmentioning
confidence: 99%
“…environmental agents, dietary factors, and lifestyle habits, accumulate, leading to aberrant-pathological changes in expression [67, 68]. Evidently, these notions should be taken into consideration for longitudinal studies in populations at high risk of developing AD [69]. Furthermore, research on incipient stages of AD might not be in conflict with other confounding factors, but as the pathology worsens, the epigenome seems to change dramatically.…”
Section: Epigenomic Technology Advancements In Admentioning
confidence: 99%
“…The shared genetic basis of EOAD and LOAD has been revealed by targeted sequencing analyses, where AD risk variants in probands ascertained from LOAD families have been identified (Cruchaga et al , 2012). Furthermore, APOE , the most well-established genetic modifier of AAO of AD, influences AAO of AD in families affected by EOAD (Marchani et al , 2010, Pastor et al , 2003, Velez et al , 2016b) and persons affected by LOAD (Naj et al , 2014). …”
Section: Introductionmentioning
confidence: 99%